Prevalence and Antibiogram of Pseudomonas aeruginosa Among Nile Tilapia and Smoked Herring, with an Emphasis on their Antibiotic Resistance Genes (blaTEM, blaSHV, blaOXA-1 and ampC) and Virulence Determinant (oprL and toxA) - Mohamed, Dina S.; Ragab, Aml M.; Ibrahim, Madiha S.; Talat , Dalia (Journal of Advanced Veterinary Research, 2023)
Bacterial diseases are one of the most challenging issues facing aquaculture sector. Pseudomonas aeruginosa (P. aeruginosa) has been regarded as one of the most significant threats to the fishing industry, which also affects public health. We aimed to elucidate the occurrence and antibiogram profile of P. aeruginosa recovered from Nile tilapia (Oreochromis niloticus) and smoked herring (Clupea harengus) with emphasis on their antibiotic resistance genes (blaTEM, blaSHV, blaOXA-1 and ampC) and virulence determinant genes (oprL and toxA). A total of 150 fish samples (110 diseased Nile tilapia, and 40 smoked herring) were collected randomly from retails of Gharbia Governorate, Egypt. The retrieved isolates were phenotypically characterized using standard methods of culturing and biochemical tests. Then, verified using molecular assay, 16S rRNA gene was detected in 100% of the tested isolates. The overall incidence of P. aeruginosa was 33.3%, out of which 45% from smoked herring and 29% from Nile Tilapia. The occurrence of P. aeruginosa in various infected organs of O. niloticus showed that the gills were the most obviously infected organ followed by kidney, liver, and spleen, respectively. A significant difference (P< 0.05) was noticed in the distribution of P. aeruginosa among O. niloticus internal organs. The phenotypic susceptibility to nine commonly used antimicrobial agents was detected using disc diffusion assay. The tested strains were extremely susceptible to ciprofloxacin, amikacin, and imipenem, whereas exhibited remarkable resistance to oxacillin, cefpodoxime, amoxicillin with clavulanic acid, ceftriaxone, and nalidixic acid. Interestingly, 100% of P. aeruginosa isolates were multiple antimicrobial resistant (MAR). Three resistance phenotypes profiles were identified with MAR index ranged from 0.4-0.5. Screening for antibiotic resistance genes revealed a diversity of Î²-lactamases in P. aeruginosa isolates, with blaTEM being the most dominant gene (100%), followed by blaSHV, blaOXA-1 and ampC with a total prevalence of 66.6% to all of them. The identified antimicrobial resistance phenotypes and genotypes were found to be significantly correlated. Subsequently, the distribution of virulence determinants in these strains was identified. These isolates had 100% prevalence of oprL and toxA virulence genes. In conclusion, the emergence of MDR P. aeruginosa in fish particularly ESBL and AmpC beta-lactamases producers could pose a potential health hazard to consumers. Thus, antimicrobial susceptibility must be continuously monitored to assess potential risks to human health. Ciprofloxacin, amikacin, and imipenem were the most efficient antibiotics for treatment of the identified P. aeruginosa, ESBL and AmpC beta-lactamases producers.